2016
DOI: 10.1111/jdv.13615
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cross‐sectional study of anxiety and depression in patients with psoriasis in Singapore

Abstract: This study demonstrates the strong psychiatric morbidity in patients with psoriasis, for which further psychiatric evaluation should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 16 publications
8
24
1
1
Order By: Relevance
“…Many clinical characteristics of psoriasis patients are reported to be correlated with psychological disorders, including depression, anxiety, and others [1, 4, 11, 14]. Partially in line with previous studies, our study demonstrated that female gender, long disease duration, and high PASI score were positively associated with depression symptoms, and female gender, large psoriasis-affected BSA, and high PASI score were positively associated with anxiety symptoms in psoriasis patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Many clinical characteristics of psoriasis patients are reported to be correlated with psychological disorders, including depression, anxiety, and others [1, 4, 11, 14]. Partially in line with previous studies, our study demonstrated that female gender, long disease duration, and high PASI score were positively associated with depression symptoms, and female gender, large psoriasis-affected BSA, and high PASI score were positively associated with anxiety symptoms in psoriasis patients.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the disease duration was longer in depressed patients compared with non-depressed patients in our study. Finally, as the indexes for evaluating psoriasis severity, the higher scores of psoriasis-affected BSA and PASI represent more severe skin conditions of psoriasis, which is positively correlated with psychiatric conditions and may exacerbate depression and anxiety in psoriasis patients [1, 4]. Additionally, more severe disease is associated with poorer quality of life, which could also exacerbate mental disorder in psoriasis patients [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there was no statistically significant correlation between age and depressive score in cases of psoriasis with GHQ ≥3. These results were supported by the study conducted by Tee et al 19 where also there was no significant corelation between anxiety and depression scores on HADS and the age of the patients. In the present study, on the correlation between age and QOL score in cases of psoriasis with GHQ ≥3, no significant relationship was found.…”
Section: Discussionsupporting
confidence: 82%
“…Je nach Studiendesign, untersuchter Population und den zugrunde gelegten diagnostischen Kriterien geben bis zu 62% der Psoriasis-Patienten depressive Symptome an und bis zu 43% der Patienten berichten von Angstgefühlen [2,3]. …”
Section: Transfer In Die Praxis Von Dr Wiebke Sondermann (Essen)unclassified